ISOLATION AND CHARACTERISTICS OF BACTERIOPHAGES SANITARY-INDICATIVE MICROORGANISMS - Monarchovich , M.A.; Galaburda, O.A.; Arashkova , A.A.; Sverchkova , N.V.; Kolomiets , E.I. (Eurasian Journal of Applied Biotechnology, 2022)
Isolated phages showed activity toward opportunistic and pathogenic bacteria of genera Escherichia (K3P1, K3P2, BIM BV-44 D) and Pseudomonas (PsP1), formed lysis zones shaped as negative homogeneous colonies with a clear-cut even edge (K3P1, PsP1, BIM BV -44 D), or negative colonies with a peripheral zone of partial lysis (K3P2). The diameter of phage plaques varied from 0,5–1,5 mm. Lytic activity spectrum of phage isolates was investigated. It was found that the studied bacteriophages displayed species specificity. Bacteriophages K3P1, K3P2 were distinguished by the highest lytic range. Differences in the isolated bacteriophages according to restriction profiles were revealed. Bacteriophage distinctions in restriction profiles were revealed. Interaction of bacteriophages with cells of bacteria of E. coli and Ps. aeruginosa was explored. The tested bacteriophage strains demonstrating lytic activity toward sanitary-indicative bacterial species may find use as disinfectants in detergents.